Standing transcutaneous surgical excision of a sialolith in an 11‐year‐old Thoroughbred mare. (20th November 2017) - Poore, L.; Smit, Y.; Williams, J.; Steenkamp, G.
Summary: An 11‐year‐old Thoroughbred mare was diagnosed with sialolithiasis of the right parotid salivary duct. A firm nonpainful subcutaneous mass was palpable in the right maxillary region adjacent to premolar 4 (tooth 108). Radiographic and ultrasonographic examinations identified a discrete mineralised ovoid mass that was hyperechoic and produced an acoustic shadow. Surgical excision of the mass was performed under standing sedation using a transcutaneous approach and the excised sialolith submitted for histopathological and mineral composition analyses. Histological examination found no evidence of a nidus at the sialolith's core. Mineral analysis of the sialolith revealed its composition to be 40% calcium phosphate (apatite) and 60% calcium carbonate. The mare recovered with no post‐operative complications and was clinically unremarkable 2 years later.